FUSARIUM HEAD BLIGHT AND MYCOTOXIN CONCENTRATIONS IN A MODERATELY RESISTANT WINTER WHEAT CULTIVAR UNDER DIFFERENT NUTRIENT REGIMES - Sobieraj, Malgorzata Glosek; Cwalina-Ambroziak, Bozena; Waskiewicz, Agnieszka; Perczak, Adam; Stepien, Arkadiusz (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Winter wheat cv. Boomer was grown in a field-plot experiment in Tomaszkowo near Olsztyn. During the growing season, the severity of Fusarium head blight (FHB was evaluated on a 5-point scale. The quantitative and qualitative composition of Fusarium fungi colonizing wheat grain was evaluated in a laboratory. The content of Fusarium mycotoxins (deoxynivalenol, DON, nivalenol, NIV, zearalenone, ZEA, fumonisins FB1 and FB2) and ergosterol (ERG) in grain was determined by high-performance liquid chromatography (HPLC). The relationships between the severity of FHB and mycotoxin concentrations in grain were determined by calculating Pearson’s correlation coefficient r in the CORR SAS procedure. The effect of microelement fertilizers on the severity of FHB, the species composition of Fusarium fungi colonizing winter wheat grains and mycotoxin concentrations in grain were determined.Analyses of winter wheat spikes revealed that FHB was less severe in 2012 (healthy ears in the NPK+Mn treatment and the lowest value of the infection index 1% was noted in the absolute control treatment) than in 2013 (the most evident symptoms of FHB in the NPK+Nano-Gro treatment – infection index of approx. 12%). Mineral fertilization, i.e. NPK, NPK with microelements (Cu, Zn, Mn) and NPK with the Nano-Gro® organic growth stimulator, reduced the production of trichothecenes, ZEA and fumonisins B1 and B2 in both years of the study. The highest levels of DON and NIV were noted in winter wheat grain in 2012 in control, control/NPK, NPK+Cu and NPK+Mn treatments. Toxin-producing fungi: Fusarium culmorum, F. poae, Gibberella avenacea, G. zeae were isolated most frequently from winter wheat grain in the above treatments. The severity of FHB was not significantly correlated with the concentrations of ERG, FB1, FB2 and ZEA in grain. A negative correlation was observed between the severity of FHB vs. DON and NIV levels in grain.